Groundwater scarcity impact on inclusiveness and women empowerment: Insights from school absenteeism of female students in two watersheds in India. Issue 11 (1st November 2016) - Kookana, Rai S; Maheshwari, Basant; Dillon, Peter; Dave, Seema H; Soni, Prahlad; Bohra, Hakimuddin; Dashora, Yogita; Purohit, Ramesh C; Ward, John; Oza, Sachin; Katara, Pratibha; Yadav, Kamal K; et al.
ABSTRACT: A survey was conducted in eight secondary schools located in two watersheds in Gujarat and Rajasthan (semi-arid region of India) to assess students' perceptions about groundwater scarcity issues and the impact of the scarcity on their educational opportunities. Survey responses to a detailed questionnaire by a cohort of students in both watersheds; school attendance records of year 8 class students (13–14 years old) and responses gathered via a socio-economic survey involving 500 families in the study area were used in the study. In both watersheds, >90% students identified groundwater scarcity as a major issue. Required to work at home or farm, about 65% students in Gujarat and 60% in Rajasthan missed school for up to 2 days/month; and a smaller proportion (∼ 30%) missed schools for 4 or more days/month. School absenteeism was found to be linked with gender; female students missed schools more frequently than their male counterpart. The school attendance records in Rajasthan showed that the frequency of female students missing schools for 5 or more days/month was on an average 2–10 times greater than that for males. The gender difference in absenteeism in all schools was statistically significant ( P < .018** ). The study highlighted that groundwater scarcity in the study area, and consequent demand on their time for household work including fetching drinking water are contributing factors towards limiting their educational and economic opportunities. Groundwater scarcity can be one of the key factors that can limit inclusiveness and empowerment of women and need to be considered in policy-making.